Desenvolvimento de metodologia eletroanalítica para a determinação de Imipramina em formulações comerciais utilizando eteltrodo de diamante dopado com Boro - Oliveira, Sâmeque do Nascimento (2010)
This research describes the development of an electroanalytical procedure proposal for the determination of tricyclic antidepressant imipramine (IMP) in commercial pharmaceutical formulations, using Boron-Doped Diamond Electrode (BDDE) and Square-Wave Voltammetry (SWV). The electrochemical oxidation of imipramine was studied in 0.04 mol L-1 Britton-Robbinson buffer solution (BR). The results using VOQ showed two well-defined oxidation peaks with potentials of 0.04 V and 0.82 V versus Ag/AgCl/Cl- 3 mol L-1 for peaks 1 and 2, respectively. For the studies’ development was used the peak 1 because it demonstrated to be more sensitive and selective. The effect of the experimental and voltammetric parameters were evaluated and the best performance was obtained in pH 7.4, pulses application frequency of potential of 100 s-1, potential increment of 2 mV and amplitude of 50 mV. Under these conditions, the analytical curves were obtained in the linear range of concentration from 1.73 x 10-7 mol L-1 to 2.53 x 10-6 mol L-1 (r = 0,9984), with detection and quantitation limits 4.35 x 10-8 mol L-1 e 1.45 x 10-7 mol L-1, respectively. The proposed method was applied with success in the determination of IMP in commercial pharmaceutical formulations and validated by comparison with standard method for determination of imipramine. The obtained results were in close agreement, at a 95% confidence level, with those obtained using an official method of the British Pharmacopoeia.